Difusão de dados baseada em atraso e energia para redes de sensores sem fio - Daniel Ludovico Guidoni (2007)
One of the most important resources in wireless sensor networks is energy, since, in general, the nodes batteries cannot be recharged. Then, all solutions to these networks must be efficient in terms of energy. The goal of this work is to design protocols to disseminate a data to all network nodes, i.e., solutions to perform broadcasting in wireless sensor networks. With this goal, it is proposed the Delay and Energy Based Broadcasting (DEBB), a protocol that combines the concepts of forwarding delay with the energy map to perform the energy-efficient broadcasting in wireless sensor networks. The basic operating of DEBB is simple and optimized to reduce the workload in sensor nodes. Simulation results revealed the efficiency of the proposed protocol in relation to the network coverage, number of transmissions and the energy consumption. The protocol presents the ability to avoid low energy regions and it is scalable when the number of low energy regions increases. Besides, DEBB presents a mechanism to reduce the latency that is the main problem of the forwarding delay algorithms.